脑磁图扫描装置和脑磁图扫描方法 (2025)
本申请提供了一种脑磁图扫描装置和脑磁图扫描方法，涉及医学成像技术领域，解决了现有坐式头盔扫描效率低的问题。该装置包括具有多个探测器插槽的探测器插槽模块，探测器插槽模块用于同步控制多个探测器插槽承载的探测器的行程。本申请提供的脑磁图扫描装置通过模块化设计，大大提高了扫描效率。该装置使受试者以卧式体位接受扫描，不仅能避免坐式扫描头部负重、移动的缺陷，也能同时对头部主动限位，进一步降低头动导致的伪迹，提高了扫描过程的稳定性和扫描精度。此外，该装置还具有优秀的易用性，在不引入额外干扰的情况下，可以便捷地使每个探测器位于适合于不同受试者的最佳扫描位置，并在扫描完成后快速复位，方便受试者移出头部。 The invention provides a magnetoencephalogram scanning device and a magnetoencephalogram scanning method, relates to the technical field of medical imaging, and solves the problem of low scanning efficiency of an existing sitting type helmet. The magnetoencephalogram scanning device comprises a detector slot module with a plurality of detector slots, wherein the detector slot module is used for synchronously controlling the strokes of detectors carried by the plurality of detector slots. According to the magnetoencephalogram scanning device provided by the invention, through modular design, the scanning efficiency is greatly improved. The device enables a subject to receive scanning in a horizontal body position, not